2008
DOI: 10.1007/s10995-008-0311-y
|View full text |Cite
|
Sign up to set email alerts
|

Infant Mortality in the Lower Mississippi Delta: Geography, Poverty and Race

Abstract: During the late 1970s and early 1980s, region, poverty and racial composition of counties all played an important part in predicting life chances for infants born in these eight states. Furthermore, Central Delta infants in counties with poverty levels of 30% or greater were significantly more likely to die than infants in other areas with the same rates of poverty, even after controlling for racial composition. The impact of regional differences was no longer significant at the ends of the subsequent two deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The health disadvantage that accompanied poverty in the study population is found throughout health research. Socioeconomic status, regardless of how it is measured (insurance status, education, household income, poverty level, wealth), has a strong graded relationship with maternal and fetal-infant health (intrauterine growth, prematurity, chronic disease, mortality, physical and mental health functioning) ( Eudy, 2009 , Harding, 2003 , McLeod and Nonnemaker, 2000 ; Nepomnyaschy, 2009 ; Walton et al, 2009 ). The relatively high poverty rate within the study county compared to the state and the nation illustrates that maternal populations such as these may have elevated exposure to this psychosocial risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The health disadvantage that accompanied poverty in the study population is found throughout health research. Socioeconomic status, regardless of how it is measured (insurance status, education, household income, poverty level, wealth), has a strong graded relationship with maternal and fetal-infant health (intrauterine growth, prematurity, chronic disease, mortality, physical and mental health functioning) ( Eudy, 2009 , Harding, 2003 , McLeod and Nonnemaker, 2000 ; Nepomnyaschy, 2009 ; Walton et al, 2009 ). The relatively high poverty rate within the study county compared to the state and the nation illustrates that maternal populations such as these may have elevated exposure to this psychosocial risk.…”
Section: Discussionmentioning
confidence: 99%
“…Within the United States, Black infants die at 2.2 times higher rate than White infants (11.6 and 5.2 deaths per 1000 live births, respectively); a gap that has remained consistent even though overall infant mortality has trended steadily downward ( Murphy et al, 2013 , Orsi et al, 2010 ). The brunt of such inequities are borne by Black populations, but disparities take a toll on all, as gaps between the least and the most advantaged affect the health of those at every strata ( Cooper et al, 2013 , Eudy, 2009 , Oishi et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…A New York State study found that the number of hospital beds per capita was negatively related to the risk of infant death from exogenous causes and all causes combined, but conversely higher per capita primary care physician rates appeared to be associated with an increased risk of infant mortality due to exogenous causes 30 . On the other hand, a recent study in the Mississippi Delta found that the number of physicians per 1,000 residents did not contribute significantly to infant mortality over and above the effects of poverty and geographic location 22 …”
Section: Risk Factors Associated With Increased Infant Mortalitymentioning
confidence: 91%
“…Infant mortality rates are known to be elevated in low‐income populations 18–21 . Poverty is associated with reduced availability of healthy food, poor sanitation in some rural areas, lowered access to quality health care, and less optimal education about proper nutrition and prenatal care 22 . Poverty also is known to interact with other factors, such as race/ethnicity and maternal education to produce higher levels of infant mortality in specific subpopulations 23 …”
Section: Risk Factors Associated With Increased Infant Mortalitymentioning
confidence: 99%
“…In 2015, approximately 5.9 million infants died before age five, with one million dying on the first day of life, another million in the first week, and 2.8 million within the first month (Marinho et al., 2020). A series of recent studies emphasize that these high levels of infant mortality are heavily concentrated among people experiencing poverty (Currie, 2009; Cutler et al., 2006; Eudy, 2009; Klasen, 2008; Mohamoud et al., 2019; Pritchard & Keen, 2016; Singh et al., 2017; Taylor‐Robinson et al., 2019). Poor socioeconomic conditions early in life adversely affect the health and development of infants.…”
Section: Introductionmentioning
confidence: 99%